KAJIAN ETNOMATEMATIKA PADA MOTIF KAIN TENUN SIKKA NUSA TENGGARA TIMUR DALAM BENTUK GEOMETRI UNTUK PEMBELAJARAN DI SEKOLAH DASAR - Regi, Benyamin; I.S. Rodriquez, Estrado (Jurnal Biogenerasi, 2024)
Ethnomathematics is used to show what is found in the social environment, which is related to the social, economic and cultural aspects of a society. We can find ethnomathematics in the process of making ikat weaving. Where the manufacture and results of ikat weaving cannot be separated from mathematical concepts. Ethnomathematics in ikat weaving can be used as a learning medium for students. This research aims to determine the application of geomathematical aspects in mathematics learning on Sikka ikat woven fabric from East Nusa Tenggara Province. This research is ethnomathematics research, qualitative descriptive research. Data was taken from two weavers at the Jata Kapa Center in Maumere. The data collection method for this research uses in-depth interviews with two weavers and an elementary school teacher. The researcher also obtained data through documentary research related to sources in the form of journals and tools used in the form of interview guides, observation sheets and documentation. Based on the results of data analysis and discussion, it was concluded that the patterns on the roseani woven fabric contain mathematical concepts, especially plane geometry in the form of rhombus patterns, triangles, parallel lines, parallelograms, squares and rectangles.